HDAC3 Mediates Cardioprotection of Remifentanil Postconditioning by Targeting GSK-3β in H9c2 Cardiomyocytes in Hypoxia/Reoxygenation Injury. Issue 2 (August 2018) - Chen, Manli; Liu, Qin; Chen, Lijian; Zhang, Lei; Cheng, Xinqi; Gu, Erwei
ABSTRACT: Background: Remifentanil postconditioning (RPC) confers robust cardioprotection against ischemia/reperfusion (I/R) injury. We recently determined that HDAC3 was involved in RPC-induced cardioprotection. However, the role of HDAC3 and its possible mechanisms in RPC-induced cardioprotection are unknown, which we aimed to evaluate in an in vitro hypoxia/reoxygenation (HR) model. Methods: Myocardium I/R injury was established after HR with H9c2 cardiomyoblasts. Cell viability and apoptosis were evaluated usingCCK-8 and flow cytometry of HR-injured cardiomyoblasts treated with or without RPC. Furthermore, effects of RPC on HDAC3 protein and mRNA expression were evaluated with Western blot and quantitative real-time PCR analyses, whereas GSK-3β expression was measured with Western blot. Results: RPC increased cell viability and reduced cell apoptosis ( P  < 0.05) in H9c2 cardiomyoblasts subjected to HR injury. In addition, RPC promoted the phosphorylation of GSK-3β at Ser9 site ( P  < 0.05) and suppressed the protein and mRNA expression of HDAC3 ( P  < 0.05). Lentiviral-transduced overexpression of HDAC3 had no significant effects on HR injury while attenuating the cardioprotective effects of RPC on cell viability and apoptosis ( P  < 0.05), GSK-3β phosphorylation ( P  < 0.05) in H9c2 cardiomyoblasts. Conclusions: RPC attenuates apoptosis in H9c2 cardiomyoblasts after HR injury by downregulating HDAC3-mediated phosphorylation of GSK-3β. Our findings suggest that HDAC3, and its cross talk function with GSK-3β, may be a promising target for myocardium I/R injury.